DOI: 10.14264/uql.2015.15
|View full text |Cite
|
Sign up to set email alerts
|

Stimulant use disorders and psychosis: prevalence, correlates and impacts

Abstract: BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 394 publications
(537 reference statements)
1
2
0
Order By: Relevance
“…The results of our study showed that methamphetamine-associated psychosis was more strongly predicted in younger subjects, similar to the results of previous studies by (Vos et al, 2010;Thomas et al, 2016). Younger age of methamphetamine use predicted younger onset of psychosis in stimulant users (Sara, 2014). The prevalence of younger patients abusing methamphetamine tends to increase in Malaysia (Mohamed et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of our study showed that methamphetamine-associated psychosis was more strongly predicted in younger subjects, similar to the results of previous studies by (Vos et al, 2010;Thomas et al, 2016). Younger age of methamphetamine use predicted younger onset of psychosis in stimulant users (Sara, 2014). The prevalence of younger patients abusing methamphetamine tends to increase in Malaysia (Mohamed et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…The findings reflect the ability of methamphetamine and amphetamine to induce psychosis in healthy people, even in the absence of genetic predisposition, by increasing dopamine levels in the brain through various mechanisms (Bramness et al, 2012). Methamphetamine inhibits the reuptake of dopamine by interacting with the dopamine transporter (DAT), interacts with the vesicular monoamine transporter 2 (VMAT2), leading to an increase in dopamine concentration in the brain, which is directly linked to the "reward centre", leading to addiction and psychosis (Sara, 2014;Curran et al, 2004;MacKenzie, 2016). Many other studies have shown that family history of mental illness was higher in methamphetamine psychosis (Ardani & Nasab, 2015;Hides et al, 2015;MacKenzie, 2016), which is in contrast to this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation